THREE YEARS FOLLOW UP REPLANTATION IN HEAVY SMOKER PATIENT: CASE REPORT - Hans Goenawan; Cahya Yustisia Hasan; Fajar Januar Mirhard; Tiara Oktavia Saputri; Bayu Anggoro Aji (Fakultas Kedokteran Gigi Unjani, 2023)
Tooth avulsion is different from all other dental injuries due to the extracorporeal situation with varying duration and degree of contamination of the teeth and the patient's systemic conditions. In a heavy-smoker patient, wound healing could be interrupted. Extra-alveolar handling, good replantation, and educating the patient could be the key to successful treatment of tooth avulsion, especially in a heavy smoker. The aim of this study is to discuss an avulsed tooth case that has been successfully treated by replantation in a heavy smoker. A 39-year-old female patient was refered to Siloam Hospital due to a dental trauma injury. The patient was in good general health, but she was a heavy smoker. Intraoral examination revealed that the maxillary left permanent central incisor was avulsed after the patient fell off in her bathroom. Replantation is a treatment of choice in this case. The avulsed tooth was stored in a saline solution. On one visit, root canal treatment was done on the avulsed tooth extra orally soon after the patient was refered to the AE department at Siloam Hospital. The avulsed tooth was replanted and fixed using an Erich arch bar to the previous position by finger pressure. Fix the Erich bar as far as possible to the distal and mesial of the avulsed tooth using circumferential wire in every single tooth. We decided to put the Erich bar from 15 to 25. The following oral hygiene cleaning, dietary instructions, and education to reduce or stop smoking during the healing process were given. Extra-alveolar handling, good replantation, good fixation, and adequate oral hygiene education are the keys to treating a tooth avulsion, even in a heavy smoker. DOI : 10.54052/jhds.v3n2.p207-216